Worldwide research trends of post-subarachnoid hemorrhage epilepsy from 1995 to 2024: a bibliometric analysis - Gui Gui; Gui Gui; Dajun Yang; Jun Ren; Jun Ren; Ruofei Liang; Ruofei Liang (Frontiers in Neurology)
ObjectiveThe present study aims to examine the current status, research hotspots, and trends of epilepsy following subarachnoid hemorrhage (SAH) by generating visual maps, and offering research directions and references in the field of post-SAH epilepsy.MethodsWe employed bibliometric methods using VOSviewer, Microsoft Excel, and SRplot to visually analyze data on post-SAH epilepsy from the Web of Science Core Collection (WoSCC). Analysis parameters included the number of papers (NP), countries/regions, institutions, authors, journals, and keywords, assessed through network mapping.ResultsOur analysis included 1,172 publications from 1995 to 2024. The annual NP showed a growing trend, with the United States contributing the highest NP (488) and demonstrating close collaborations with other countries/regions. Harvard University in the United States had the highest institutional output, with 62 papers. The most prolific author was Jan Claassen, with 35 publications, while Neurocritical Care was the journal with the highest NP (51). The primary disciplinary category was Clinical Neurology. Keywords such as ‘inflammation,’ ‘prevalence,’ and ‘delayed cerebral ischemia’ (DCI) emerged as recent research hotspots.ConclusionOver the past three decades, there has been a significant upward trend in the annual NP on post-SAH epilepsy. The United States has maintained a leading position in this field. Current research primarily focuses on the pathogenesis, with particular attention to ‘inflammation’ and ‘DCI’.